2021
DOI: 10.1183/16000617.0045-2021
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer is also a hereditary disease

Abstract: Pathogenic genetic variants (formerly called mutations) present in the germline of some individuals are associated with a clinically relevant increased risk of developing lung cancer. These germline pathogenic variants are hereditary and are transmitted in an autosomal dominant fashion. There are two major lung cancer susceptibility syndromes, and both seem to be specifically associated with the adenocarcinoma subtype. Li-Fraumeni syndrome is caused by variants in the TP53 tumour-suppressor gene. Carriers are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 92 publications
0
23
0
1
Order By: Relevance
“…The histopathological UIP fibrosis pattern predisposes to pulmonary cancerous lesions [ 19 ]. Genetic factors contributing to cancer susceptibility and also predisposing to IPF include SFTPA1 and SFTPA2 [ 20 ].…”
Section: Epidemiology and Risk Factors Of Lung Cancer In Ild Patientsmentioning
confidence: 99%
“…The histopathological UIP fibrosis pattern predisposes to pulmonary cancerous lesions [ 19 ]. Genetic factors contributing to cancer susceptibility and also predisposing to IPF include SFTPA1 and SFTPA2 [ 20 ].…”
Section: Epidemiology and Risk Factors Of Lung Cancer In Ild Patientsmentioning
confidence: 99%
“…A subset of lung cancers do have a hereditary origin, for example, in Li-Fraumeni and the EGFR susceptibility syndrome. 3 Recently, an association between BRCA2 and lung cancer was suggested in a large Chinese study with a 0.8% PV prevalence in patients with advanced non–small-cell lung cancer. 4 Furthermore, a recent study concluded that lung cancer occurred significantly earlier in BRCA2 PVs carriers compared with noncarriers by approximately 12 years (95% CI, 2.5 to 20.6).…”
Section: To the Editormentioning
confidence: 99%
“…Mutations of a single or several nucleotides in human genome are responsible for major hereditary health problems ( Benusiglio et al, 2021 ; Samuelson et al, 2021 ; Xiao et al, 2021 ; Chen et al, 2022 ; Cobo et al, 2022 ). To date, about 7,000 hereditary diseases are estimated to be caused by monogenic mutations ( Claussnitzer et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%